Antioxidant responses of black glutinous rice to drought and salinity stresses at different growth stages - Rudiyanto Yosefine Fetik; Alfiana Okta Hadina; Putri Anandita Linggar; Rizkiantoro Ridho; Siswoyo Tri Agus (Open Agriculture)
Black glutinous rice is a local pigmented rice that attracts the interest of many people due to its high nutritional value. While cultivating, black glutinous rice may experience abiotic stresses, such as drought and salinity threat. Drought and salinity may lead to oxidative stress, which leads to the overproduction of reactive oxygen species (ROS). Moreover, the enzymatic defense mechanism of black glutinous rice against ROS, which depends on the stress type and the plant’s growth stages, remains unclear. This study was performed to determine the defense response of black glutinous rice to drought (10% PEG) and salinity (80 mM NaCl) stresses at different growth stages (vegetative [V], reproductive [R], and vegetative+reproductive [V+R]) and then continued to recover at every growth stage. This study showed enhanced accumulation of ROS under drought and salinity stresses, with the reproductive stage presenting the highest accumulation of hydrogen peroxide and malondialdehyde. In contrast, the recovery phase decreased the ROS accumulation. The antioxidant enzyme activities (catalase [CAT], ascorbate peroxidase [APX], and peroxidase [POD]) showed different responses between the biochemical and transcript levels of antioxidant genes (OsCATA, OsAPX, and OsPOD) during stress and in the recovery phase. These results indicate the foundation for elucidating the defense mechanism response of black glutinous rice to different growth stages and stresses, such as drought and salinity.